Cross-national variation in determinants of climate change concern. Issue 5 (29th July 2019) - Lewis, Gregory B.; Palm, Risa; Feng, Bo
ABSTRACT: Our understanding of the determinants of public concern about climate change relies heavily on survey research in the United States. But can those findings be generalized to the rest of the world? Analysis of the Pew Research Center's 2015 Global Attitudes Survey shows fairly similar patterns in the English-speaking Western democracies and, to a lesser extent, western Europe, but party identification and political ideology matter much less in most of the globe, and demographic factors have very different impacts. Female, younger, and less religious people tend to worry more about climate change in English-speaking Western democracies. In most of the world, however, concern is only weakly correlated with gender, rises with age and religiosity, and is more strongly correlated with education. A new measure of commitment to democratic values proved to be the most consistent predictor of concern globally.